Profissionalidade docente : narrativa de um grupo de professoras alfabetizadoras da rede municipal de Várzea Grande – MT - Silva, Rosilene Paula da (2020)
This research, of master degree level, entitled “Teacher professionalism: Narrative of a Group of Literacy Teacher of the City School of Várzea Grande/MT”, linked to the Post-Graduation Program in Education of the Federal University of Mato Grosso, articulated to the Study and Research Group in Politics and Teacher Formation – hereby GEPForDoc, has as aim to comprehend, from the narratives, how Literacy teachers (re)signify their experiences in the process of teacher professionalism. According to Roldão (2005; 2008), the professionalism is formed by several attributes, that are constituted in the social context, therefore allows to distinguish the professions and their relevance, this being a progressive process of professional construction that follows throughout the active life of the teacher. It is a qualitative research that approaches the theoretical assumptions of narrative research. The research context is the EMEB Honorato Pedroso de Barros of City School of Várzea Grande/MT, with the collaboration of four Literacy teachers. In the research, we present three thematic axes, which are: 1) Experiences in the insertion in the teacher profession; 2) Acting in Literacy: knowledge and learning; and 3) The professional identities constituted in the development of professionalism. The narrative is considered as interaction process with the other in which the meaning given to the lived experienced, narrated by the participant teachers, will allow the narrative researcher to be part of this process with formative/investigative movement, generating learning and (re)signification in the constitution of teacher professionalism. The theoretical basis that contemplates the research work is founded in the discussions about the concept of professional development and of the teacher professionalism, the concept and history of Literacy in Brazil, as well as the insertion in teacher profession and of the knowledge and teacher learning. The main authors who sustain the research are Clandinin and Connelly (2011) in dialogue with other authors, such as Nóvoa (1992, 1995, 1997, 2009), Dewey (1976), Day (2001), Vaillant e Marcelo (2012), Roldão (2005), Contreras (2002), Mizukami (2004 e 2005/2006), Mortatti (1999, 2000, 2004, 2010), Soares (1985, 2011, 2013). When narrating their trajectory, each teacher had the opportunity to remember and to reflect, in the course of their teacher action, the meaning of the experiences, besides being able to have a look about the process of constitution of teacher professionalism as Literacy teacher. It is also interesting to know the educational politics of educational system as working conditions, the different functions performed in the profession, as well as how their family and personal history contributed in the constitution of “Me, the teacher”. The research narratives reveal the complexity of the literacy teacher’s work, how the relationships with the school context influence the performance of pedagogical practice throughout her profession, showing that the time of experience in the classroom, makes it possible to reframe their practices, with their own analysis regarding the educational programs implemented, to the school space, building flexibility in the action of planning and expanding their autonomy. Several changes in teaching action occur in view of the difficulties in the educational system in the search to effect learning, in addition to highlighting in their narratives, two principles of pedagogical actions: the importance of collective work and the concern with students' learning. Thus, the senses and meanings are constructed in this process of constitution of the teaching professionality in a continuous way and integrated with the personal and professional dimensions.